2017
DOI: 10.1590/s1679-45082017ao4082
|View full text |Cite
|
Sign up to set email alerts
|

Study of the relation between body weight and functional limitations and pain in patients with knee osteoarthritis

Abstract: Objective To assess the influence of the body weight in functional capacity and pain of adult and elderly individuals with knee osteoarthritis.Methods The sample consisted of 107 adult and elderly patients with knee osteoarthritis divided into two groups (adequate weight/adiposity and excessive weight/adiposity) according to body mass index and percent of body fat mass, assessed by electric bioimpedance. Subjects were evaluated for functional mobility (Timed Up and Go Test), pain, stiffness and function (Weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 20 publications
(24 reference statements)
0
24
0
2
Order By: Relevance
“…Several studies have assessed the effect of weight loss and physical function on knee OA patients (21-23). Weight loss using aerobic exercises as well as proper diet are recommended in guidelines for knee OA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed the effect of weight loss and physical function on knee OA patients (21-23). Weight loss using aerobic exercises as well as proper diet are recommended in guidelines for knee OA patients.…”
Section: Discussionmentioning
confidence: 99%
“…The degenerative changes within the joint cartilage depend on age [6,11,13]. Pop et al by analyzing occurrence of gonarthrosis, they found that its frequency increases with age [14].…”
Section: Discussionmentioning
confidence: 99%
“…Independente do grau da artrite na pesquisa de Rosales et al, (2014) foi constatado que o grupo avaliado em estudo que diminuiu o IMC apresentou melhora da dor e da função, e aqueles que o IMC aumentou teve uma piora tanto da dor quanto da função. Além do IMC, o excesso de adiposidade também pode estar associado a maior sensibilidade a dor (ALFIERI et al, 2017;PACCA et al, 2018).…”
Section: Discussionunclassified